2010
DOI: 10.1016/j.jvoice.2008.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Electroglottographic Evaluation of Age and Gender Effects During Sustained Phonation and Connected Speech

Abstract: The aim of the present study was to evaluate the effects of age and gender on selected vocal fold vibratory behaviors during vowel prolongation and connected speech using electroglottography (EGG). Forty-six young and older individuals (23 males and 23 females) with normal voices participated in this study. EGG parameters including fundamental frequency and contact quotient were measured during sustained vowel prolongation and connected speech tasks. Significant age-by-gender interactions were found for both p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 24 publications
7
34
1
7
Order By: Relevance
“…We also confirmed several effects of age on voice acoustic measures, including a significant decrease in F0 values in women (Honjo and Isshiki 1980;Torre and Barlow 2009;Ma and Love 2010;Da Silva et al 2011;Stathopoulos et al 2011;Dehqan et al 2013;Goy et al 2013), and no change in f0 values in men (Stathopoulos et al 2011;Goy et al 2013). For MPT, consistent with previous reports, we showed that it was unaffected by age (Maslan et al 2011;Goy et al 2013), even though MPT should depend upon several factors such as, respiratory volumes, airflow rate, task comprehension, and maximal effort, factors that one would expect to decline with age.…”
Section: Effects Of Age On Voice Acoustic Measuressupporting
confidence: 91%
See 1 more Smart Citation
“…We also confirmed several effects of age on voice acoustic measures, including a significant decrease in F0 values in women (Honjo and Isshiki 1980;Torre and Barlow 2009;Ma and Love 2010;Da Silva et al 2011;Stathopoulos et al 2011;Dehqan et al 2013;Goy et al 2013), and no change in f0 values in men (Stathopoulos et al 2011;Goy et al 2013). For MPT, consistent with previous reports, we showed that it was unaffected by age (Maslan et al 2011;Goy et al 2013), even though MPT should depend upon several factors such as, respiratory volumes, airflow rate, task comprehension, and maximal effort, factors that one would expect to decline with age.…”
Section: Effects Of Age On Voice Acoustic Measuressupporting
confidence: 91%
“…These changes have an impact on voice production and quality (Mazzetto de Menezes et al 2014). Indeed, aging negatively affects voice stability and amplitude in a sex-dependent manner (Linville and Fisher 1985;Ma and Love 2010;Dehqan et al 2013;Goy et al 2013). For instance, men generally show a gradual increase in fundamental frequency (f0) with age (Honjo and Isshiki 1980;Harnsberger et al 2008;Torre and Barlow 2009;Ma and Love 2010;Dehqan et al 2013), while women exhibit a decrease in f0 with age (Honjo and Isshiki 1980;Torre and Barlow 2009;Ma and Love 2010;Da Silva et al 2011;Dehqan et al 2013;Goy et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Aline Mansueto Mourão (1) , Iara Barreto Bassi (2) , Ana Cristina Côrtes Gama (3) RESUMO Objetivo: comparar os resultados da avaliação eletroglotográfica entre mulheres adultas com laudo otorrinolaringológico de nódulos vocais e presença de fenda glótica com mulheres sem alterações laríngeas. Método: trata-se de 20 mulheres, sendo 10 com exame otorrinolaringológico de nódulo vocal, associado à fenda glótica, e 10 com vozes avaliadas na análise perceptivo-auditiva como neutras e avaliação otorrinolaringológica sem alteração laríngea.…”
Section: Electroglottograpical Evaluation Of Dysphonic Women With Masunclassified
“…(2) Fonoaudióloga; Mestranda em Saúde e Trabalho: Saúde Pública pela Universidade Federal de Minas Gerais -UFMG -Belo Horizonte (MG), Brasil. (3) Fonoaudióloga; Professora Associada do Departamento de Fonoaudiologia da Universidade Federal de Minas Gerais -UFMG -Belo Horizonte (MG), Brasil.…”
Section: Descritoresunclassified
See 1 more Smart Citation